Lifelong Learning : Policies, Practices, and Programs - Humber Coll. of Applied Arts and Technology, Toronto (Ontario). School of Media Studies; Hatton, Michael J. (S.l. : Distributed by ERIC Clearinghouse, 1997)
The 26 articles in this book focus on lifelong learning policies, practices, and programs in 13 Asia Pacific countries. The following papers are included: "Half a Revolution: A Brief Survey of Lifelong Learning in New Zealand" (P. Methven and J. Hansen); "HRD in a Multicultural Workplace: The Need for Lifelong Learning" (M. Ogisu-Kamiya); "Lifelong Learning: The Whole DAMN Cycle. A Singapore Perspective" (D. Pan); "Advancing Lifelong Learning through Adult Education Policy in Chinese Taipei" (C. Wang); "Articulation and Transfer: Critical Contributions to Lifelong Learning" (F. Kintzer); "Trends in Hong Kong University Management: Towards a Lifelong Learning Paradigm" (S. Liu); "Lifelong Learning in a Developed and Developing Economy" (C. Beaupre); "An Empirical Framework for Implementing Lifelong Learning Systems" (L. Seng and L. Hwee); "Lifelong Learning in Malaysia" (Y. Leong); "Lifelong Learning and Basic Literacy: Adult Literacy Education in Chinese Taipei" (C. Ho); "Schools as Centres of Lifelong Learning for All" (J. Chapman and D. Aspin); "Lifelong Learning in the United States and Hong Kong: Before 1997 and After" (A. Yee and J. Cheng); "Lifelong Learning: An Instrument for Improving School Education in Japan?" (Y. Sawano); "Lifelong Learning in Hong Kong" (G. Lee); "Lifelong Learning and Cultural Identity: Canada's Native People" (B. Rice and J. Steckley); "Non-Formal Education in the Philippines: A Fundamental Step Towards Lifelong Learning" (C. Gonzales and C. Pijano); "Distance Education: A Key Strategy for Lifelong Learning in Chinese Taipei" (J. Huang); "Prior Learning Assessment: U.S. Experience Facilitating Lifelong Learning" (C. Mann); "Thoughts on a Regional Approach for Lifelong Learning" (J. Yoshio); "Contribution of SMP Terbuka Toward Lifelong Learning in Indonesia" (A. Sadiman and R. Rahardjo); "Two Wheels for Lifelong Learning in Korea: Credit Banking & Multimedia Technology" (M. Pak); "Lifelong Learning, Workforce Development and Economic Success" (A. Lee); "From Supplemental Education to Lifelong Learning in Chinese Taipei" (C. Lee); "Recent Developments in Japan's Lifelong Learning Society" (A. Makino); "Lifelong Learning in the People's Republic of China" (H. Wu and Q. Ye); and "A Pure Theory of Lifelong Learning" (M. Hatton). (BCY)
Availability: School of Media Studies, Humber College, 205 Humber College Boulevard, Toronto, Ontario, Canada M9W 5L7.
Sponsoring Agency: Canadian International Development Agency, Ottawa (Ontario).
Sponsoring Agency: Association of Canadian Community Colleges.
ERIC Note: For individual articles, see JC 970 459-483. Endorsed and supported by the Asia Pacific Economic Cooperation Forum's Human Resources Development Working Group.
Microfiche.
Keywords: Adult Education; Articulation (Education); Economic Development; Educational Objectives; Educational Policy; Educational Practices; Foreign Countries; Labor Force Development; Lifelong Learning; Models; National Programs; Postsecondary Education; Program Descriptions; Role of Education; Asia Pacific Region; Books; Collected Works, General